Inequalities of Different Metrics for Differentiable Periodic Functions - Kofanov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We prove the following sharp inequality of different metrics:$$\begin{array}{cc}\hfill {\left\Vert x\right\Vert}_q\le {\left\Vert {\varphi}_r\right\Vert}_q{\left(\frac{{\left\Vert x\right\Vert}_p}{{\left\Vert {\varphi}_r\right\Vert}_p}\right)}^{\frac{r+1/q}{r+1/p}}{\left\Vert {x}^{(r)}\right\Vert}_{\infty}^{\frac{1/p-1/q}{r+1/p}},\hfill & \hfill q>p>0,\hfill \end{array}$$for 2π -periodic functions $x ∈ L_{∞}^r$ satisfying the condition$$L{(x)}_p\le {2}^{1/p}{\left\Vert x\right\Vert}_p,$$where$$L{(x)}_p:= \sup \left\{{\left\Vert x\right\Vert}_{L_p\left[a,b\right]}:a,b\in \left[0,2\pi \right],\kern0.5em \left|x(t)\right|>0,\kern0.5em t\in \left(a,b\right)\right\},$$and $φ_r$ is the Euler spline of order $r$. As a special case, we establish the Nikol’skii-type sharp inequalities for polynomials and polynomial splines satisfying the condition (A).